REKAYASA DAN UJI KINERJA PROTOTIPE DESTILATOR SKALA LABORATORIUM - Suhardi Suhardi (JURNAL AGROTEKNOLOGI, 2015)
Laboratory equipment is quite expensive so amount of the equipment in the laboratory is very limited, considering the procurement of laboratory equipment is not always needs budgete annually by the college. It takes creativity laboratory manager to improve the performance of laboratory equipment so that the equipment can support educational activities. This research used two steps were: (1) design of destilator prototipe, include: functional and structural design, (2) performance test include: functional test, test alcohol produce, the rate of destilation, dan Efficiency of distillation. Desain and performance test was processed in agricultural engineering laboratory, agricultural technology faculty of Jember Univiersity. The result showed that as a functional and structural design it was can operate with dimensions were, bolier capacity 1 liter, height of destiltor prototype 52cm. At the performance test of alcohol produced showed that the higher of alcohol produced without the perforated plate disc on factionating column was 82.5%. The higher of distilation rate with three the perforated plate discs was 5,75 ml/minute. The higher of distillation efficiency with three the perforated plate discs was 97.41%.Keywords: performance tests, efficiency of distillation, alcohol, distilator prototype